2018
DOI: 10.1186/s13148-018-0543-7
|View full text |Cite
|
Sign up to set email alerts
|

Association of internal smoking dose with blood DNA methylation in three racial/ethnic populations

Abstract: BackgroundLung cancer is the leading cause of cancer-related death. While cigarette smoking is the primary cause of this malignancy, risk differs across racial/ethnic groups. For the same number of cigarettes smoked, Native Hawaiians compared to whites are at greater risk and Japanese Americans are at lower risk of developing lung cancer. DNA methylation of specific CpG sites (e.g., in AHRR and F2RL3) is the most common blood epigenetic modification associated with smoking status. However, the influence of int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 52 publications
1
29
1
1
Order By: Relevance
“…The lower correlations may also suggest that the measured DNAmAge of participants are being confounded by environmental factors beyond what studies have adjusted for. This is a particularly important point, given that DNA methylation levels are dynamic and may be influenced by environmental factors such as stress [84] and smoking [85].…”
Section: Discussionmentioning
confidence: 99%
“…The lower correlations may also suggest that the measured DNAmAge of participants are being confounded by environmental factors beyond what studies have adjusted for. This is a particularly important point, given that DNA methylation levels are dynamic and may be influenced by environmental factors such as stress [84] and smoking [85].…”
Section: Discussionmentioning
confidence: 99%
“…Smoking remains a major preventable cause of morbidity and mortality worldwide and has been shown to associate extensively with DNA methylation changes across the genome as evidenced by several epigenome-wide association studies (EWAS) [1]. Almost all EWAS so far, including a recent large meta-analysis ( N = 15,907) [2], assessed the association between DNA methylation and self-reported smoking status or smoking quantity [323]. Self-reported smoking status and quantity, however, are prone to inaccuracies due to reporting bias (usually under reporting or recall bias) [24].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the changes in DNA itself, many epigenetic changes are reversible, which provides an optimistic outlook for the treatment of the diseases [18]. Environmental factors can affect the methylation of DNA promoter such as smoking [19], life stress [20], dietary [21], etc. For example, Park SL et al found that internal smoking dose was associated with increased DNA methylation in circulating leukocytes at specific sites in Native Hawaiian smokers [19].…”
Section: Discussionmentioning
confidence: 99%
“…Environmental factors can affect the methylation of DNA promoter such as smoking [19], life stress [20], dietary [21], etc. For example, Park SL et al found that internal smoking dose was associated with increased DNA methylation in circulating leukocytes at specific sites in Native Hawaiian smokers [19]. In a cross-sectional study conducted in 5186 Australian adult participants, the authors suggested that dietary intake of one-carbon metabolism nutrients was associated with blood DNA methylation [21].…”
Section: Discussionmentioning
confidence: 99%